The subject without support: rise and fall of contemporary subjectivity - Gobantes Bilbao, Maite; Tarodo-Cortes, Dan (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
This text serves as an introduction to the dossier entitled "Discourses of Contemporary Subjectivity: From Poetics to Video Games". This monograph of the scientific journal Tropelías proposes to approach the phenomenon of subjectivity, its emergence or -in some cases- absence, in speeches and texts of diverse nature that constantly flow today. It is commonly accepted that literature has helped to shape the subjectivity of the citizen since the eighteenth century and that cinema, in the twentieth century, did the same. In the second decade of the XXI, the payroll of texts that penetrate the subject seems to have multiplied; only two examples: video games and television series, which coexist with traditional ones.